FRI0013 Activation of the Non-Canonical NF-κB Pathway in Dendritic Cells Upregulates Extrathymic Autoimmune Regulator (AIRE) Expression. (9th June 2015) - Huitema, L.F.A.; Helder, B.; Noort, A.-R.; Lebre, M.C.; Boon, L.; Kroese, F.G.; Tas, S.W.
Abstract : Background: The nuclear factor (NF)-κB family of transcription factors has a key role in the regulation of inflammation. Ligation of CD40 on dendritic cells can induce early production of inflammatory mediators via the canonical NF-κB pathway, as well as late expression of the of the immunoregulatory enzyme indoleamine 2, 3-dioxygenase (IDO) via non-canonical NF-κB signalling [1]. Non-canonical NF-κB signalling via CD40 is also crucially important for the expression of Autoimmune Regulator (AIRE) in the thymus. AIRE is a transcription factor that is involved in thymic negative selection of autoreactive T cells and therefore is pivotal in the establishment of central tolerance. We have recently found extrathymic AIRE-expressing cells (eTACs) that may play a role in peripheral tolerance in rheumatoid arthritis synovial tissue and glandular tissue from Sjogren's syndrome patients. eTACs are mainly antigen presenting cells, including DC, that can inactivate peripheral T cell responses. However, until now the stimuli that can induce extrathymic AIRE expression in DC are largely unknown. Objectives: To study whether activation of the non-canonical NF-κB pathway stimulates AIRE expression in human monocyte-derived DC. Methods: Monocyte-derived DC were generated by culturing healthy donor monocytes for 6 days with GM-CSF and IL-4. Maturation was induced by addition of LPS or the non-canonical NF-κB stimuli such as lymphotoxin, LIGHT, RANKL or anti-CD40 for 48 hours. AIRE and IDO expression was quantified by qPCR and cleavage of p100 into p52 was analyzed by Western blot. Presence of AIRE protein was analyzed by Western blot and immunofluorescence staining. Results: Anti-CD40 and RANKL stimulation of DC resulted in cleavage of p100 into p52, upregulation of AIRE RNA and AIRE protein. Confocal microscopy revealed that AIRE protein was localised in the nucleus. Interestingly, this was accompanied by increased expression of the IDO in these cells. Conclusions: CD40 and RANKL stimulation in DC activates the non-canonical NF-κB pathway and simultaneously upregulates AIRE and IDO expression. The functional significance of peripheral AIRE expression in DC requires further investigation, but it may be associated with immunoregulatory properties. Eventually, this knowledge may be exploited to develop new treatment modalities for patients with autoimmune diseases, including DC-based therapies. References: Tas SW, Vervoordeldonk MJ, Hajji N, Schuitemaker JH, van der Sluijs KF, May MJ, et al. Noncanonical NF-kappaB signaling in dendritic cells is required for indoleamine 2, 3-dioxygenase (IDO) induction and immune regulation. Blood 2007;110:1540-9. Disclosure of Interest: None declared